2013
DOI: 10.1590/abd1806-4841.20131930
|View full text |Cite
|
Sign up to set email alerts
|

Behçet disease in association with Budd-Chiari syndrome and multiple thrombosis - Case report

Abstract: Behçet's disease is a chronic inflammatory disease of unknown aetiology, characterized by recurrent oral and genital aphthous ulcerations, uveitis, skin lesions and other multisystem affections associated with vasculitis. Different types of vessels, predominantly veins, can be affected in Behçet's disease. The frequency of vascular lesions in Behçet's disease, such as superficial and deep venous thromboses, arterial aneurysms and occlusions, ranges between 7-29%. Budd-Chiari syndrome is a rare and serious comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Strong positive test results for antiphospholipid antibodies were present in 3 patients. TS has also been reported in association with an idiopathic hypereosinophilic syndrome,15 inflammatory bowel disease,16 Kimura disease,17 and Behcet disease 18. In our case, no definite precipitating event and none of the underlying prothrombotic states described above were identified.…”
Section: Discussionsupporting
confidence: 56%
“…Strong positive test results for antiphospholipid antibodies were present in 3 patients. TS has also been reported in association with an idiopathic hypereosinophilic syndrome,15 inflammatory bowel disease,16 Kimura disease,17 and Behcet disease 18. In our case, no definite precipitating event and none of the underlying prothrombotic states described above were identified.…”
Section: Discussionsupporting
confidence: 56%
“…The most common causes are hypercoagulation states [ 21 ]. The frequency of vascular involvement (superficial and deep venous thrombosis, arterial aneurysms, and occlusions) in BD ranges from 7% to 29% [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of BCS in patients with BD was reported at between 1.1% and 5.8% [ 7 , 20 , 24 , 25 ]. Uskudar et al [ 22 ] reported in their series of 75 patients that web was 16%, hydatid cyst was 12%, and BD was 9% responsible in BCS etiology in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 Behçet disease is associated with an increased risk for VTE, and, to a lesser extent, arterial occlusions and aneurysms. 62 The most common thrombotic complication in patients with Behçet disease is DVT, and patients frequently have recurrent events.…”
Section: Other Disordersmentioning
confidence: 99%